3D reactive surface scan utilising a robot with rigidly mounted range sensors. Issue 12 (27th October 2020) - Kim, Jonghoek
Abstract : This article considers autonomous scanning (coverage) control of a two‐dimensional (2D) surface embedded in 3D environments. The author uses a robot with rigidly mounted range sensors. The robot can measure its depth (height for aerial robot) and has narrow aperture rays near the central ray which is normal to the longitudinal axis of the robot. The goal of the robot is to scan (cover) a 2D surface embedded in 3D environments within a given range of depths. To achieve robust scanning performance in 3D environments, this article presents sliding mode controllers as well as switching controllers. According to the author's knowledge, this article is unique in developing 3D reactive scanning controllers considering a robot equipped with narrow aperture rays near the central ray. Extensive simulation results are utilised to demonstrate the effectiveness of the proposed controllers.